The role of outdoor advertising in consumer behaviour in implementing the goals of sustainable development: a case study of Lithuania - Samašonok, Kristina; Jarašūnienė, Aldona; Išoraitė, Margarita (Business, Management and Economics Engineering, 2025)
The article discusses the possibilities of managing consumer behavior in the context of implementing the goals of sustainable development formation through outdoor advertising and the assessment of the impact of outdoor advertising on consumer behaviour formation. Research objective – to determine the impact of outdoor advertising in consumer behaviour in implementing the goals of sustainable development. The research methods employed include descriptive analysis, quantitative analysis, and statistical techniques. The research was conducted from September 10, 2024, to September 24, 2024, based on a Lithuanian case study (N = 396). When applying a quantitative research strategy the obtained highest average estimates show that illuminated signs, advertising on outdoor video screens and large format posters in advertisements spread the message and have a great impact on consumer behaviour when implementing the goals of sustainable development. It was also found out that according to the majority of participants, the images in advertising (pictures, paintings, etc.), advertising design and outdoor advertising originality, as well as advertising content and its informative nature are the factors shaping consumer behaviour when implementing the goals of sustainable development. The use of a convenience sample, coupled with an imbalance in terms of gender and age distribution, limited the generalizability of the conclusions. There- fore, the spheres of further researches could be expanded with more representative samples and including the elements of qualitative method into the survey (e.g., open questions, group discussion (in Focus group) etc.), regression modelling and factor analysis would provide more insights and supplement quantitative conclusions. The research results provided valuable in- sights about the role of different types of outdoor advertising and its impact on consumers of different ages when implementing the goals of sustainable development and on the basis of the Lithuanian case could be easily extrapolated to other contexts while expanding the spheres of further researches, both at the national level and with cross-border samples.